Subthreshold micropulse diode laser treatment in diabetic macular oedema. Issue 9 (17th August 2004) - Laursen, M L; Moeller, F; Sander, B; Sjoelie, A K
Abstract : Background/aim: Enlargement of laser scars after retinal argon laser photocoagulation can give rise to deterioration in visual acuity. Subthreshold micropulse diode laser may decrease this risk. The aim of this study was to compare the effectiveness of subthreshold micropulse diode laser (810 nm) and conventional argon laser (514 nm) photocoagulation for the treatment of clinically significant macular oedema in diabetic patients. Methods: 23 eyes of 16 patients were randomised to either treatment. Follow up was conducted for a minimum of 5 months. Changes in visual acuity and macular oedema measured by optical coherence tomography were examined. Results: Visual acuity remained stable in all treatment groups throughout the observation period. Changes in retinal thickness were small both foveally and perifoveally. In patients with focal macular oedema a significant reduction in retinal thickness (9% ∼ −26 μm, p = 0.02) was seen foveally 3 months after diode laser photocoagulation. Conclusion: Subthreshold micropulse diode laser and conventional argon laser treatment showed an equally good effect on visual acuity. Subthreshold micropulse diode laser showed a stabilising or even improving effect on macular oedema. The combination of primary diode laser and supplementary argon laser might be particularly favourable in reducing diabetic macular oedema.